Trade Creation and Diversion Effects under the Free Trade Agreement between Peru and the United States: A Gravitational Analysis - Arrieta Padilla, Gabriel Lewis (2021)
This paper is oriented to quantify the trade creation and diversion effects in the Free Trade Agreement (FTA) between Peru and the United States. For that purpose, using a disaggregated database at the 10-digit level for Peruvian goods with intervals of 3-years between 2002 and 2018, this article adopts a three-dummy variable methodology that allows the identification of intra-bloc and extra-bloc effects. In addition, a theoretically-founded gravity equation is employed with the incorporation of country-time and time-invariant fixed effects in order to solve common econometric specification problems, such as lack of multilateral resistance terms in modelling, heteroscedasticity of trade data, inclusion of zero trade flows, and endogeneity of trade policy. Estimating with the PPML method for the complete sample and among types of goods (group 1: raw materials and intermediate goods, and group 2: consumer and capital goods), the main results show that the Peru-US FTA generates intra-bloc trade creation for the entire sample and two groups of goods separately. In addition, the FTA produces export trade diversion for the complete sample and group 2, while import trade creation for both groups. In overall, the Peru-USA FTA is an “intra-bloc trade creation agreement” that boosted bilateral trade flows. These effects are considered in order to formulate some policy recommendations for improving the results of this Peruvian FTA.